Synthesis, biological activity, molecular docking studies of a novel series of 3-Aryl-7H-thiazolo[3, 2-b]-1, 2, 4-triazin-7-one derivatives as the acetylcholinesterase inhibitors. Issue 7 (9th April 2021) - Jin, Zhe; Zhang, Chao; Liu, Miao; Jiao, Simeng; Zhao, Jing; Liu, Xiaoping; Lin, Huangquan; Chi-cheong Wan, David; Hu, Chun
Abstract: The acetylcholinesterase inhibitors play a critical role in the drug therapy for Alzheimer's disease. In this study, twenty-nine novel 3-aryl-7 H -thiazolo[3, 2- b ]-1, 2, 4-triazin-7-one derivatives were synthesized and assayed for their human acetylcholinesterase ( h AChE) inhibitory activities. Inhibitory ratio values of seventeen compounds were above 55% with 4c having the highest value as 77.19%. The compounds with the halogen atoms in the aromatic ring, and N, N -diethylamino or N, N -dimethylamino groups in the side chains at C-3 positions exhibited good inhibitory activity. SAR study was carried out by means of molecular docking technique. According to molecular docking results, the common interacting site for all compounds were found to be peripheral anionic site whereas highly active compounds were interacting with the catalytic active site too. HIGHLIGHTS: A novel series of 3-aryl-7 H -thiazolo[3, 2- b ]-1, 2, 4-triazin-7-one derivatives were synthesized and assayed for their human acetylcholinesterase ( h AChE) inhibitory activities. The SAR study of the target 3-aryl-7 H -thiazolo[3, 2- b ]-1, 2, 4-triazin-7-one derivatives was summarized. The active sites in the acetylcholinesterase were analyzed by molecular docking technique. Communicated by Ramaswamy H. Sarma